Interactive Effects of Drought-Tolerant Varieties and Fertilizer Microdosing on Maize Yield, Nutrients Use Efficiency, and Profitability in the Sub-Humid Region of Benin - Tovihoudji, Pierre G.; Bagri, B. Moukaïla; Batamoussi Hermann, Michel; Tonnang, Z. E. Henri; Akponikpè, P. B. Irénikatché (Frontiers in Agronomy, 2022)
In sub-Saharan Africa, smallholder farming systems continue to record very low yields despite the availability of appropriate crop management technologies. A two-years field experiment was conducted in 2018 and 2019 at the Agricultural Research Station of Northern Benin to evaluate the response of growth, grain yield and components and resource use efficiency of different drought-tolerant (DT) maize varieties (TZEE-W POP STR QPM, TZE-Y POP STR, 2008Syn EE-W DT STR, 2000Syn EE-W of 80-90 days cycle) compared to DMR ESR W, a drought-susceptible (DS) variety of 90 days cycle) under different fertilizer options [no fertilizer control, micro-dosing options 1 (MD1, 25 kg N ha−1 , 4 kg P ha−1) option 2 (MD2, 25 kg N ha−1 , 8 kg P ha−1), option 3 (MD3, 35 kg N ha−1 , 8 kg P ha−1) and broadcast fertilizer at recommended rate (RR, 76 kg N ha−1 , 13 kg P ha−1). Generally, combining micro-dosing with DT varieties shown very good performance by increasing leaf area and biomass by 71% and 85% at anthesis compared to conventional practice. Micro-dosing increase grain and stover yields by 171% and 98% compared to unfertilized control with generally no difference between MD3 and RR treatments. Also, the DT varieties obtained the best yields (+19%) with the highest observed with the TZE Y variety. However, no significant interaction was found between varieties and fertilization for grain yield in opposite to stover yield which exhibited a significant interaction. Microdose fertilization and DT varieties showed high efficiencies of nutrients and rainwater use. Likewise, DT varieties and micro-dosing fertilization show a high economics performance and are revealed to be an excellent mean to increase smallholder farmer’s income. The results of the current study demonstrated that there is considerable potential for smallholder farmers of northern Benin to improve maize productivity by means of DT varieties and fertilizer micro-dosing. However, it is important to evaluate the stability of the yields under these management options in farmer’s fields by taking into account climatic, soil and soci-economic conditions.